Strategi Guru Dalam Memotivasi Belajar Siswa Kelas V SD Negeri 1007 Tanjung Baringin - Harahap, Nurhalimah; Erma Wani Nasution; Era Mutiah (Yayasan Perguruan Kampus, 2025)
The purpose of this study was to determine: 1) teacher strategies in motivating fifth grade students of SD Negeri 1007 Tanjung Baringin to learn. 2) supporting and inhibiting factors for teachers in motivating fifth grade students of SD Negeri 1007 Tanjung Baringin to learn. This study falls under the category of field research. Techniques for gathering data include documentation, interviews, and observation. The subjects in the study are teacher strategies in motivating student learning, while the objects to be studied are teachers who teach in grade V, namely religious teachers, and fifth grade students. With data collection techniques using interviews, observation and documentation. Data reduction, data display, and conclusion-making are all methods of data analysis. Based on the results of the study, teacher strategies in motivating fifth grade students of SD Negeri 1007 Tanjung Baringin by giving quizzes and rewards. Strategies that can increase enthusiasm and a sense of competition so that students compete in understanding the subject matter in order to answer quizzes and rewards. There are two supporting factors for teachers in motivating fifth grade students of SD Negeri 1007 Tanjung Baringin, specifically internal components, or those that originate from inside pupils, such their physical well-being. Furthermore, external factors or factors originating from outside the students themselves, such as teachers providing teaching aids to help students better understand the lessons delivered, such as pictures or videos. One of the inhibiting factors for teachers in motivating students to learn at SD Negeri 1007 Tanjung Baringin is the limited availability of learning facilities, a less conducive environment, other classes often making noise and students coming in and out disturbing other classes that are studying next to them.